Successful cervicothoracic esophageal stricture treatment with partial sternectomy and a pedicled TAAP flap: A case report - Li, Baofei; Wang, Haiyang; Liu, Jun; Mu, Xiaosong; Xu, Feng; Deng, Di; Qiao, Yixin; Wang, Shipin; Chen, Fei (Frontiers in Surgery, 2023)
Postoperative benign esophageal anastomotic leakage and stenosis are common complications after esophagectomy. Treatment options for anastomosis stenosis include endoscopic mechanical dilation, dilation combined steroid injection, incisional therapy, stent placement, and self-bougienage. However, long-segmental cervicothoracic esophageal stenosis and cutaneous fistula are always refractory to conservative treatments and are clinical challenging. When lesions extend well below the thoracic inlet, transthoracic esophagectomy and alimentary canal reconstruction seem to be the common choice but susceptible to perioperative mortality and donor-site sequelae, especially for patients with poor health conditions. In this report, we present a novel surgical approach for cervicothoracic esophageal stenosis and fistula via partial sternectomy and reconstructed with a pedicled thoraco-acromial artery perforator (TAAP) flap. No recurrence or complications occurred throughout 3 months of follow-up. This case adds new aspects to the treatment of anastomotic stenosis.